DAMPAK PANDEMI COVID-19 TERHADAP KEMISKINAN DI PROVINSI KEPULAUAN RIAU - Hartoto; Hasim As'ari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This paper aims to examine the impact of the Covid-19 Pandemic on Poverty inthe Riau Islands Province. The writing uses secondary data published by BPSRiau Islands Province in 2019-2021. The data analysis method uses the ratio ofmeasurement of poverty indicators. From the results and discussion it wasconcluded that the COVID-19 pandemic in the Riau Islands Province had animpact on: (1) The poor population in the Riau Islands Province seen from thenumber and percentage of the poor tended to increase; (2) the Gini coefficient ofthe poor in the Riau Islands Province tends to increase, so that there is aninequality in income distribution; (3) Looking at the development of the values ofP0, P1, and P2, it can be seen that poverty alleviation in rural areas requiresgreater cost, time and attention when compared to poverty in urban areas; and(4) poverty reduction programs implemented by the government, both centraland regional, can reduce the number and percentage of poor people. Therefore it is recommended that poverty reduction programs implemented by thegovernment, both central and regional, can be continued.